2022
DOI: 10.1111/are.15787
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus ) induced by different feeding modes: Effects on growth, serum biochemical indices, intestinal digestion and hepatic metabolism of glucose and lipid

Abstract: A 56‐day feeding trial was conducted to investigate metabolic responses of hybrid grouper (Epinephelus fuscoguttatus × ♂ E. lanceolatus) induced by different feeding modes. The experimental groupers were divided into three feeding modes as follows: continuous feeding group (8 weeks, C group), prolonged starvation group (8 weeks, S group) and refeeding group (starving for 4 weeks + refeeding for 4 weeks, R group). The results show that prolonged starvation had negative effect on growth, yet refeeding caused com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 119 publications
(166 reference statements)
0
3
1
Order By: Relevance
“…These results indicated that starvation can inhibit the activities of glycolysis-related enzymes, and the change trends were positively correlated with blood GLU levels. However, GK activity showed a significant increase under starvation, but returned to normal after refeeding for 7 d, which was contrary to findings in Oncorhynchus mykiss (Kirchner et al, 2005), Sparus aurata (Metoń et al, 2004), and hybrid grouper (Chen et al, 2022).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…These results indicated that starvation can inhibit the activities of glycolysis-related enzymes, and the change trends were positively correlated with blood GLU levels. However, GK activity showed a significant increase under starvation, but returned to normal after refeeding for 7 d, which was contrary to findings in Oncorhynchus mykiss (Kirchner et al, 2005), Sparus aurata (Metoń et al, 2004), and hybrid grouper (Chen et al, 2022).…”
Section: Discussioncontrasting
confidence: 77%
“…For example, the muscle transcriptomes of Larimichthys crocea (Qian et al, 2016), Oncorhynchus mykiss (Rescan et al, 2007), and Lctalurus punctatus (Liu et al, 2013) have been analyzed during starvation and refeeding. Starvation can promote the metabolism of energy materials, such as body fat and protein, and significantly increase the expression of hormone synthesisrelated genes to resist stress damage (Chen et al, 2022;Elbialy et al, 2022). Liver tissue is an important site for nutrient metabolism, and plays an important regulatory role in animals during starvation (Pilkis and Granner, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Skin may also be an important site for asthma attacks, and the impaired skin barrier function may lead to the invasion of allergens, thereby triggering Th2-like sensitization and asthma attacks [21,22]. Gluconeogenesis refers to the process of converting nonsugar compounds into glucose or glycogen, which helps maintain the body's balance [23]. FBP1 is one of the rate-limiting enzymes in gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the GO enrichment analysis, we found that ATP generation from ADP, purine nucleoside diphosphate metabolic process, ADP metabolic process, ribonucleoside diphosphate metabolic process, and glycolytic process were upregulated in the early stage of transportation and downregulated in the final stage of transportation. ATP generation from ADP and ADP metabolic process, catalyzed by pyruvate kinase, was identified as the second substrate-level phosphorylation reaction of glycolysis, serving as a compensatory mechanism for energy cost during anaerobic glycolysis . Muscle and hepatopancreas are recognized as primary sites for glycogen storage .…”
Section: Resultsmentioning
confidence: 99%